2012
DOI: 10.1590/s0102-695x2011005000207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wound healing activity of Ammannia baccifera and Blepharis maderaspatensis leaf extracts on rats

Abstract: Wound healing activity of the leaf extracts of Ammannia baccifera L., Lythraceae, and Blepharis maderaspatensis (L.) B.Heyne ex Roth., Acanthaceae, was investigated by excision and incision wound healing models in rats. A phytochemical screening was done to determine the major constituents of the chloroform, ethyl acetate and ethanolic fractions of ethanolic leaf extracts. The excision and incision models were used to assess the effect of the plant extracts on wound healing in rats. Phytochemical screening rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The curative properties of Blepharis species paved the way for researchers to explore their therapeutic properties. Herein, several pharmacological properties for other plant species from the genus Blepharis have been reported, such as anti-inflammatory and anti-nociceptive properties [6], wound healing activities [7], and gastroprotective [8] effects of B. maderaspatensis (L.) B.Heyne ex Roth. Moreover, other studies reported antioxidant activity for B. maderaspatensis and B. molluginifolia Pers.…”
Section: Introductionmentioning
confidence: 99%
“…The curative properties of Blepharis species paved the way for researchers to explore their therapeutic properties. Herein, several pharmacological properties for other plant species from the genus Blepharis have been reported, such as anti-inflammatory and anti-nociceptive properties [6], wound healing activities [7], and gastroprotective [8] effects of B. maderaspatensis (L.) B.Heyne ex Roth. Moreover, other studies reported antioxidant activity for B. maderaspatensis and B. molluginifolia Pers.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Lythraceae wound healing properties, the ethanolic extract of the leaves of Ammannia baccifera, which contains flavonoids and tannins, induced improvement in the different phases of wound healing process, including collagen synthesis, maturation, wound contraction and epithelization (Rajasekaran et al 2012). The extract of Lawsonia inermis L. leaves provided a reduction in the period of epithelization, high resistance to skin rupture, increase in granulation tissue, reduction of 71% in wound area, increase of collagen and fibroblasts and little inflammatory infiltrate.…”
Section: Pacari Extract (10%) Pmentioning
confidence: 99%
“…(Janning et al 2011); Punica granatum L. (Hayouni et al 2011;Ismail et al 2012); Ammannia baccifera L. and Blepharis maderaspatensis (L.) B. Heyne ex Roth. (Rajasekaran et al 2012). Regarding L. pacari, there was a single report using plants extracted in Brazilian Mato Grosso region, in which wound healing effects were detected both in vitro and in vivo (Pereira et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The acute dermal toxicity study [24] was carried out in adult albino rats of both sexes by "fix dose" method of OECD (Organization for Economic Co-operation and Development) Guideline No.434 (OECD, 1987). The temperature of the experimental animal room was 22 °C ( ± 2) and the relative humidity was 30-70 %, where the lightings were artificial and the sequence was 12 h light and 12 h dark.…”
Section: Acute Dermal Toxicity -Fixed Dosementioning
confidence: 99%